Smoking Prevention and Cessation - La Torre, Giuseppe (Springer US : Imprint: Springer, 2013)
The cravings, the compulsive behaviors, the potential fatal health consequences--once considered relatively harmless, tobacco use is now understood to have addictive properties similar to those of hard drugs. Dependence on tobacco and nicotine from smoking, chewing, or other means affects millions around the world, and for countless people it remains resistant to efforts to quit despite the level of intervention or number of attempts.   Smoking Prevention and Cessation addresses this longstanding problem on various biological, societal, and psychological fronts. This extensively researched volume traces the mechanics of smoking initiation, nicotine dependence and withdrawal, and motivation to quit. Chapters analyze smoking as a global public health issue, review the epidemiology of smoking-related disease, and evaluate prevention and cessation interventions (pharmacology included) as applied to different settings and populations. The detailed, data-rich presentation gives readers a rounded, realistic understanding of smoking on a worldwide level as the book:   Introduces measurement tools for gauging nicotine dependence. Examines the media in tobacco advertising and smoking prevention messages. Analyzes "what works" in prevention approaches. Compares the efficacy of cessation interventions. Pinpoints issues specific to smoking among health professionals and youth. Reviews economic, bioethics, and policy issues related to smoking.   Researchers and graduate students in public health, health promotion, behavioral medicine, and smoking cessation will find Smoking Prevention and Cessation a unique reference packed with evidence-based insights and practical, workable ideas.